Future foods: Is it possible to design a healthier and more sustainable food supply?. Issue 3 (3rd September 2020) - McClements, D. J.
Abstract: There is increasing concern about the negative impact of the modern food system on the health of both us and our planet. As the global population continues to increase, we need to feed everyone without irreparably harming the environment. Moreover, the food produced should be affordable, convenient, safe, nutritious and sustainable. This article reviews some of the recent technological advances being employed to design foods to improve their healthiness and sustainability. In particular, emphasis is placed on how processed foods can be redesigned to make them healthier by altering the nature and structural organisation of their constituents to modulate the way they behave inside our bodies. This includes reducing the levels of undesirable food constituents, such as saturated fat, salt and sugar, as well as incorporating health‐promoting ingredients such as vitamins, minerals, bioactive compounds, prebiotics and probiotics. Moreover, foods are being designed to be masticated and digested more slowly or to release their constituents at particular locations along our gastrointestinal tract, which may help to fight obesity and diabetes by reducing appetite. A focus will also be placed on some of the new technologies being developed to create alternatives to animal products, such as meat, milk and egg, which should reduce the amount of meat consumed and alleviate some of its negative impacts on our environment.